Turkey : Financial Sector Assessment Program: detailed assessment of Observance-Assessment of Observance of the CPMI-IOSCO Principles for Financial Market Infrastructure. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2017)
This paper presents an assessment of observance of the CPMI-IOSCO (Committee on Payments and Market Infrastructures-International Organization for Securities Commissions) principles for financial market infrastructures in Turkey. The electronic funds transfer system in Turkey broadly observes the risk management framework and liquidity risk management, default management, and operational risk management principles. It partially observes the tiered participation principle. The rest are observed or not applicable. The electronic securities transfer system broadly observes the risk management framework, liquidity, default management, and operational risk principles; the rest are observed or not applicable.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet